Debate: Conduct disorder, like all psychiatric diagnoses, is not a diagnosis. Issue 3 (18th July 2022) - Timimi, Sami
Abstract : Like all psychiatric diagnoses, conduct disorder (CD) relies on entirely subjective foundations. Without empirical anchors, we are left with descriptors that cannot help us identify cases that share universalisable commonalities beyond those imposed on them by the subjectivity of the diagnoser. This article highlights how mistaking a descriptive category for a diagnosis has resulted in, including for CD, a failure to improve scientific knowledge or clinical outcomes. For progress to occur the dominance of a technical diagnostic paradigm in psychiatry must be over‐turned and CD will then lie on the slag heap of history alongside the other consumable brands mis‐labelled as a psychiatric diagnosis.